Determination of the botanical composition of black rhinoceros (Diceros bicornis) dung using the rbcL gene as a molecular marker, and analysis of antioxidant and phenolic content of its browse - Bulani, Siyavuya Ishmael (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 2007)
The black rhinoceros remains one of the world's extremely endangered species despite a variety of policies to protect it. The black rhinoceros population at the Great Fish River Reserve (GFRR) in the Eastern Cape in South Africa has increased steadily since their re-introduction in 1986. This megaherbivore is a browser, with a diet obtained largely from the short and medium succulent thicket of the GFRR. Knowledge of the preferential diet of the black rhinoceros on the reserve is an important factor for the effective management of the land and the herbivores that compete for its resources. The dietary preferences of the black rhinoceros at the reserve have been established using backtracking methods. In this study the rbcL gene was used to establish an rbcL gene database of the plants from the GFRR and determine the botanical composition of the black rhinoceros dung from the GFRR. Due to the limited number of rbcL gene plant sequences from the GFRR deposited in the GenBank database, 18 plant species from the GFRR were sequenced. Sequence analyses between the partial rbcL gene sequences generated were able to distinguish between plants down to species level. Plant species from the family Euphorbiaceae and Fabaceae showed sequence variation at intra-specific level compared to those of Tiliaceae which were more conserved. The generated rbcL gene sequences from seasonal dung samples were compared to the rbcL gene sequenced from 18 plant species obtained from the GFRR and those from the GenBank database. A wide range of plant species were identified from the dung samples. There were no major differences in botanical composition between the dung samples, except that Grewia spp. were found to dominate in almost all seasons. The results obtained on the free radical scavenging activity of the extracts against 2,2-Diphenyl-l-picrylhydrazyl (DPPH) increased in the order of methanol > ethyl acetate > chloroform. The DPPH free radical scavenging activity of the methanol plant extracts increased in the order Brachylaena elliptica > Plumbago auriculata > Grewia robusta > Azima tetracantha. Methanol extracts on the TLC plate sprayed with FeÂ³â º-2,4,6-Tri-2-pyridyl-s-triazine (TPTZ) showed that the compounds present in the extracts react differently to ferric ion, with most compounds unable to reduce ferric ion. Furthermore the methanol extracts were able to exhibit reduction potentials vs. Ag/AgCl at low concentrations. The compounds in the extracts were shown to be phenolic acids and flavonoid glycosides.
Keywords: Black rhinoceros -- Food; Black rhinoceros -- South Africa -- Eastern Cape; Browse (Animal food) -- Analysis -- South Africa -- Eastern Cape; Plant ecology -- South Africa -- Eastern Cape; Genetic markers; Black rhinoceros -- Manure -- Analysis; Phenols; Antioxidants